SEARCH EFFICIENCY FUNCTION-PSO COMBINATION FORBLIND IMAGE RESTORATION - TOUMI, A .; RECHID, N.; TALEB-AHMED, A .; BENMAHAMME, K. (Courrier du Savoir; Vol. 13 (2012): Courrier du Savoir)
In this work we propose, for the first time, a combined method for blind image restoration. This combination is based on PSO and the integration in it of the search efficiency function that represent the optimal searching strategy elaborated by honeybees when searching for food, and its use for the first time in image processing, to carry out the restoration operation of the only blurred images and blurred and noisy ones. The results we got were excellent.